Dispute Resolution Mechanism Between Hospitals and Patients in the Framework of National Health Mediation - Putri Naylarizki Lasamano; Khansah Mutia Hasan; Nur Amalia Arsad (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2026)
This study aims to analyze the dispute resolution mechanism between hospitals and patients within the framework of national health mediation, in the midst of the challenges of the Indonesian health system, with the existence of Health Law Number 17 of 2023, it is hoped that medical dispute resolution can be carried out efficiently and humanely through mediation. Mediation offers a non-litigation approach that prioritizes relationship restoration and restorative justice, although it still faces various obstacles, such as a lack of understanding and trained mediators. This study uses a normative juridical method with qualitative analysis of laws and regulations and medical dispute resolution practices. The results show that mediation can be an effective alternative to reduce the burden on the courts, provided it is supported by a good understanding by all parties involved and to strengthen the application of mediation and restorative justice principles in the context of health disputes in Indonesia